Systems engineering : principles and practice - Kossiakoff, Alexander, 1914-2005 (Wiley series in systems engineering and management ;, 2011)
"Systems Engineering Principles and Practice is a national standard textbook for the study of traditional systems engineering for advanced undergraduate and graduate students. It addresses the need for an introductory overview, first-text for the development and acquisition of complex technical systems. The material is well organized, readable and fundamental to learning how to think like a systems engineer and carry out best practices in the field. Since systems engineering is still developing as a discipline, there have been new concepts and practices that have entered the field since the text was published in 2003. As an increasing number of students have used the text, topics have been discovered that would benefit from expansion, integration and clarification. The proposed second edition will be developed by colleagues of the original authors to upgrade this unique interdisciplinary guide to systems engineering to maintain relevance and currency in this rapidly changing and demanding field"--